THE CHALLENGES AND PROSPECTS OF RECYCLING IN EGYPT - Mohamed , Ahmed Abdelaziz (International Journal of Allied Research in Economics (IJARE), 2023)
Solid waste management (SWM) is a critical issue in Egypt, where the country generates approximately 90 million tons of solid waste annually, only 12% of which is recycled. This study examines the challenges facing SWM in Egypt and explores the potential of recycling as a solution to these challenges. The study found that the main challenges facing SWM in Egypt include: Lack of infrastructure: Egypt's SWM system is outdated and inefficient, with inadequate collection, transportation, and disposal facilities. Low public awareness: Many Egyptians are not aware of the importance of recycling or how to do it properly. Lack of government support: The Egyptian government has not made SWM a priority, and there is a lack of funding and resources for SWM programs. The study found that recycling can help to address some of these challenges. Recycling can reduce the amount of waste that goes to landfills, which can help to protect the environment and improve public health. Recycling can also create jobs and boost the economy. The study concludes that recycling is a promising solution to the challenges facing SWM in Egypt. However, the study also found that there are a number of factors that need to be addressed in order to make recycling more successful in Egypt, including: Increasing public awareness of the importance of recycling Improving the infrastructure for recycling Providing financial incentives for recycling Enacting legislation to promote recycling